2008
DOI: 10.1111/j.1529-8817.2008.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

TWO SNOW SPECIES OF THE QUADRIFLAGELLATE GREEN ALGACHLAINOMONAS(CHLOROPHYTA, VOLVOCALES): ULTRASTRUCTURE AND PHYLOGENETIC POSITION WITHIN THE CHLOROMONAS CLADE1

Abstract: The quadriflagellate snow alga Chlainomonas Christen, distributed in New Zealand and North America, has several unusual structural attributes. A process assumed to be cytokinesis involves extrusion of protoplasm from the parent through a narrow canal, C. kolii (J. T. Hardy et Curl) Hoham produces a net-like outer envelope rather than a cell wall, and the flagellar basal apparatus of Chlainomonas consists of two semi-independent pairs of basal bodies. Structural connections between basal body pairs appear minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 47 publications
(125 reference statements)
4
59
1
Order By: Relevance
“…However, resolution of a clade corresponding to subclade 2 of Clade A (Hoham et al, 2002) was low (only 55-78% bootstrap values in MP and ME analyses). The quadriflagellate genus Chlainomonas was included in subclade 2 by Novis et al (2008). Our Japanese samples/strains and four North American Chloromonas species (Cr.…”
Section: Molecular Phylogenymentioning
confidence: 99%
“…However, resolution of a clade corresponding to subclade 2 of Clade A (Hoham et al, 2002) was low (only 55-78% bootstrap values in MP and ME analyses). The quadriflagellate genus Chlainomonas was included in subclade 2 by Novis et al (2008). Our Japanese samples/strains and four North American Chloromonas species (Cr.…”
Section: Molecular Phylogenymentioning
confidence: 99%
“…reticulata (Goroschankin) Gobi, belongs to the Chloromonas clade, all species within this clade were classified as Chloromonas based on their characteristic chloroplast morphology under LM (Prö schold et al 2001). However, recent studies have demonstrated that the Chloromonas lineage, Chloromonadinia (Nakada et al 2008a), includes two morphologically different genera, Chlainomonas Christen, which has four flagella and a swollen or gelatinous cell wall separated from the protoplast (Novis et al 2008), and Gloeomonas G.A. Klebs, which has two separated flagellar bases .…”
Section: Introductionmentioning
confidence: 98%
“…C. kolii was described as a snow alga by HOHAM (1974a), who re-arranged Trachelomonas kolii (Euglenales) into Chlorophyta, as Chlainomonas kolii. This same alga was described in snow samples from Canada, in the NW Pacific Mountains of the USA, and in Mt Philistine, New Zealand (NOVIS 2002, NOVIS et al 2008. Chlainomonas rubra (HOHAM 1974b) was identified in snow in Tirole, N. Island of New Zealand, the Pacific Northwest USA, Wenatchee Natl For., Washington, and Mt.…”
Section: Syn Sphaerellopsis Rubra Stein Et Brooke 1964mentioning
confidence: 97%
“…Maybe Chlainomonas was derived from the fusion of biflagellate cells or is a diploid component of a biflagellate phase (sexual reproduction was not seen). The flagellar basal apparatus was also organized into two distinct pairs of basal bodies that lack connections (NOVIS et al 2008). The alga is very sensitive to temperature, and can only live at 0-4°C (HOHAM 1975).…”
Section: Syn Sphaerellopsis Rubra Stein Et Brooke 1964mentioning
confidence: 99%
See 1 more Smart Citation